2006
DOI: 10.1177/1368430206067559
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Team Identification in the Dissimilarity-Conflict Relationship

Abstract: Nutzungsbedingungen Prashant Bordia University of South AustraliaThis study examined the role of team identification in the dissimilarity and conflict relationship. We tested competing predictions that team identification would either mediate or moderate the positive associations between visible (age, gender and ethnic background), professional (background) and value dissimilarity and task and relationship conflict. Data was collected from 27 MBA student teams twice during a semester. Multilevel modelling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 84 publications
(153 reference statements)
3
55
2
Order By: Relevance
“…Following previous research, we controlled for team size (Hobman & Bordia, ; Tushman & Nadler, ). Team size was assessed by asking respondent leaders to indicate the number of team members.…”
Section: Methodsmentioning
confidence: 99%
“…Following previous research, we controlled for team size (Hobman & Bordia, ; Tushman & Nadler, ). Team size was assessed by asking respondent leaders to indicate the number of team members.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Harrison et al (2002) found that time mitigates the negative effects of surface-level diversity on team social integration, whereas it intensifies the negative effects of deep-level diversity. Similarly, Hobman and Bordia (2006) reported that the effects of visible and professional dissimilarity on conflict diminish over time. Thus, the implications of diversity dimensions examined in the present study may also change over time, perhaps holding shifting effects on both the intervening organizational processes and performance.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Team workers feel more comfortable working with the group they identify with (Eckel and Grossman, 2005;Northcraft et al, 1996), consequently boosting their team performance. Strong team identity encourages team workers to behave according to team norms and conventions (Branscombe et al, 1999;Hobman and Bordia, 2006). The presence of team identity (which emphasizes team-based values) enhances the performance of functionally diverse teams (Jehn and Bezrukova, 2004).…”
Section: Research Model and Hypothesesmentioning
confidence: 97%